A Close Relationship: Britain and Oman since 1750 - Owtram, Francis (Qatar Digital Library, 2014)
Played out against Oman’s imposing geographical position, the British relationship with Oman has changed from that of allies against common foe, through informal British imperial influence to an important trading and strategic partner today.
Keywords: Relations – Oman – Royaume-Uni

Britain and the Development of Professional Security Forces in the Gulf Arab States, 1921-71: Local Forces and Informal Empire - Rossiter, Ash (University of Exeter, 2014)
Keywords: Relations – Oman – Royaume-Uni